Pemetaan Kawasan Lahan Pertanian Pangan Berkelanjutan di Kuta Utara dan Mengwi Berbasis Penginderaan Jauh dan Sistem Informasi Geografis - OKTAFIANTI, KARTIKA DEWI; LANYA, INDAYATI; TRIGUNASIH, NI MADE (Agrotrop : Journal on Agriculture Science; Vol 11 No 2 (2021), 2021)
Mapping of Sustainable Food Agricultural Land at North Kuta and Mengwi Districts Based on Remote Sensing and Geographical Information System . Sustainable Food Agricultural Land (LP2B) is a field of agricultural land designated to be protected and developed consistently in order to produce staple food for national food independence, resilience and sovereignty. The Badung Regency Government has determined the area and location of LP2B but it has not been accompanied by a spatial information map. This study aims to map subak rice fields in 2019 as well as mapping of LP2B based on the physical conditions of the area and the environment in North Kuta and Mengwi Districts based on remote sensing and GIS. The method used consists of image interpretation, field survey and numerical classification. The results showed that the distribution of subak rice fields in North Kuta and Mengwi Districts was 4967.22 ha. The distribution of rice fields in North Kuta District is 850.15 ha and in Mengwi District is 4117.07 ha. In the classification of LP2B areas, the recommended area is model 1 (234.88 ha), model 2 (939.76 ha) and model 3 (2048.63 ha). The recommendation areas are in model 1 (1489.91 ha), model 2 (1101.52 ha) and model 3 (2047.53 ha). The conditional recommendation area is in model 1 (2969.50 ha), model 2 (2048.49 ha) and model 3 (873.39 ha). Not recommended area in model 1 (270.81 ha), model 2 (875.33 ha) and model 3 (0 ha).